A poverty-inequality trade-off? - Ravallion, Martin, 1952- 1952- (Policy research working paper, 2005)
"The idea that developing countries face a trade-off between poverty and inequality has had considerable influence on thinking about development policy. The experience of developing countries in the 1990s does not, however, reveal any sign of a systematic trade-off between measures of absolute poverty and relative inequality. Indeed, falling inequality tends to come with falling poverty incidence. And rising inequality appears more likely to be putting a brake on poverty reduction than to be facilitating it. However, there is evidence of a trade-off for absolute inequality, suggesting that those who want a lower absolute gap between the rich and the poor must in general be willing to see lower absolute levels of living for poor people. "--World Bank web site